2011
DOI: 10.1177/1362168810388721
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the cultural portfolio project on cultural and EFL learning in Taiwan’s EFL college classes

Abstract: Learning about foreign language (FL) cultures is becoming an important objective in the FL curricula and national standards of different countries throughout the world. The purposes of the study were to examine the effects of the cultural portfolio project on (1) students’ specific aspects of development of cultural knowledge and change in perception of native English speakers and their cultures; (2) students’ self-awareness, evaluation, and modification of stereotypes toward the target cultures; and (3) stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 17 publications
1
13
0
2
Order By: Relevance
“…The result indicates that this teaching paradigm is not more efficient in obtaining factual information in comparison with traditional direct instruction teaching, which should be improved in the future. However after analyzing the online discussion forum posts and oral presentations in class, we found that the students have expanded and deepened their understandings by modifying or eliminating cultural stereotypes, and this result is in agreement with previous findings (Byon, 2007;Su, 2011). Admittedly, cultural stereotypes are helpful in shaping attitudes and behaviors toward other races and cultures in some respects, but more often than not it involves false or misleading generalizations which would have detrimental effect on social interaction and communication.…”
Section: A the Change In Cognitive Aspect Of Iccsupporting
confidence: 90%
“…The result indicates that this teaching paradigm is not more efficient in obtaining factual information in comparison with traditional direct instruction teaching, which should be improved in the future. However after analyzing the online discussion forum posts and oral presentations in class, we found that the students have expanded and deepened their understandings by modifying or eliminating cultural stereotypes, and this result is in agreement with previous findings (Byon, 2007;Su, 2011). Admittedly, cultural stereotypes are helpful in shaping attitudes and behaviors toward other races and cultures in some respects, but more often than not it involves false or misleading generalizations which would have detrimental effect on social interaction and communication.…”
Section: A the Change In Cognitive Aspect Of Iccsupporting
confidence: 90%
“…They were truly motivated at generating ideas by searching from many sources such as textbooks, internet sources, TV, film, and video (Baker, 2012). In addition, Chen Su (2011) also confirmed that the subject of study was asked to recognize and re-evaluate stereotypical images portrayed in movies, TV series, and soap operas. One of essays' titles was taken from the film 'Pride and Prejudice'.…”
Section: Discussionmentioning
confidence: 81%
“…During interaction with the native speakers through different technological media, students change their attitudes towards their own culture and the culture of the target language. Su in [21] explains what happened to Taiwan students after interacting with English speakers through media. The students modified some of the elements of their culture after self-reflection, changed their own culture, their original hypothesis about English culture, change their misconception and stereotypes, respect their cultural differences and diversity and change from ethnocentrism views to ethnorelativism.…”
Section: Technology Enhances Changes In Attitude In Intercultural Pmentioning
confidence: 99%